Fire, mortality and resprouting in forest species at Sierra Norte de Puebla - Gómez-Mendoza, Félix Francisco; Rodríguez-Trejo, Dante Arturo (Instituto de Ecología, A.C., 2021)
Forest fires are increasing world-wide because of the global warming. So is necessary to understand better its effects to achieve an appropriate fire management. The objective of this work was to evaluate and to model the probabilities of both, mortality (Pm) and resprouting (Pr), on Pinus montezumae, P. teocote, P. patula, Quercus spp. (Q. crassifolia, Q. rugosa and Q. crassipes), Arbutus xalapensis and Alnus acuminata nine months after a forest fire in the ejido Michac, municipality of Chignahuapan, Puebla, Mexico. Were utilized logistic models and the estimations were made with the SAS program. It was possible to obtain robust models of Pm for one species (two models) and Pr models for three species (seven models). The Pm was inversely related to height and diameter to breast height in P. montezumae. For the Pr, there was an inverse relationship with Alt and Dn for P. montezumae, Quercus spp. and Arbutus xalapensis, as well as a direct relationship with percentage of crown fire affected in P. montezumae (all models with p value of the variables in models ≤ 0.05, confidence limits without including the value 1, concordance ≥ 40%, and goodness-of-fit test with p > 0.05). Despite the fire severity, the studied species show fire traits, as resprouting ability, that demonstrate its survival. This kind of information is useful to estimate fire-related tree mortality, for prescribed burns, to choose sites for fuel management, and to decide the convenience of conducting reforestation and restoration works.